2018
DOI: 10.18203/2320-1770.ijrcog20181902
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Foley’s catheter with PGE2 gel and Foley’s catheter with PGE2 gel with extra amniotic saline infusion for labour induction

Abstract: Background: Induction of labour is initiation of uterine contractions before the onset in order to vaginally deliver the foetoplacental unit. Common reasons for induction of labour are post-term and hypertensive disorders of pregnancy. The purpose of this study was to compare the efficacy of Foley catheter with intra cervical PGE2 gel and Foley catheter with PGE2 gel with extra amniotic saline infusion for induction of labour.Methods: The clinical trial was conducted from November 2016 to April 2017 at Karnata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…16 Several other regional and international studies have shown similar results. [17][18][19][20] Studies done in Pakistan have demonstrated the effectiveness of PGE2. 21 A recent study comparing four different types of induction showed that foley catheter with or without PGE2 is less effective as compared to PGE2 alone in achieving vaginal delivery as well well as induction to delivery interval.…”
Section: Discussionmentioning
confidence: 99%
“…16 Several other regional and international studies have shown similar results. [17][18][19][20] Studies done in Pakistan have demonstrated the effectiveness of PGE2. 21 A recent study comparing four different types of induction showed that foley catheter with or without PGE2 is less effective as compared to PGE2 alone in achieving vaginal delivery as well well as induction to delivery interval.…”
Section: Discussionmentioning
confidence: 99%